Pengaruh Perbedaan Jenis Pemanis dan Bahan Baku Terhadap Karakteristik dari Sirup Nanas - Adhamatika, Adhima; Putri, Destiana Adinda (Food Scientia : Journal of Food Science and Technology, 2023)
One of the processed products from pineapple is syrup. However, the use of natural ingredients such as fruit in processing syrup has weaknesses, both in terms of changes in color, taste, aroma and appearance. Therefore, when making pineapple syrup, flavorings are often used. The aim of this research is to increase the use of pineapple fruit and determine the differences in the quality of pineapple syrup produced with different types of sweeteners and types of ingredients in making pineapple syrup. The method used was a Randomized Block Factorial Design with 2 factors, namely the type of sweetener (sucrose, sucrose and glucose syrup) and the type of ingredient (pineapple flesh, pineapple synthetic flavors). The results showed that differences in the type of sweetener and type of ingredients had a significant effect on color (L*, a*, b*), viscosity, pH, total dissolved solids, water content, vitamin C and total acids, and sensory attributes (color, aroma, taste, and texture). The best treatment was obtained in the SG1 formulation using sucrose and glucose syrup sweetener and pineapple flesh. The quality characteristics of of this syrup are that it has an L* value 36.44; a* 24.21; b* 50.45; viscosity 94.89 cP; pH 4.53; TPT 33.66 ºBrix; water content 55.52%; vitamin C 7.25 mg/100g; total acid 4.05%; aroma 4.20; color 3.80; taste 4.20; and texture 4.33. This formulation can be developed into alternative use of the pineapple commodity that has a functional value.